A Feasibility study on a Burn Rehabilitation Center - Coscolluela, Pia T.; Macabitas, Hanny June A.; Quiambao, Pauline M. (Diliman, Quezon City College of Engineering, 1995)
This paper contains a feasibility study on a Burn Rehabilitation Center. This kind of institution has yet to be established in the country. It is a response to the ever increasing need for physical therapy and all its forms in the country. Specifically, the Center's services are geared towards the rehabilitation of medically stable burn victims. The first part of the paper consists of a market study that aims to establish the amount and nature of available demand for the service. The target area is the National Capital Region. Since the service is new, the potential market includes all burn victims in this area. Burn injuries are classified as occupational and regular, the latter being those occurring at any place other than the workplace. An analysis of the data collected for several years shows a random behavior, prompting the use of only averages in all the succeeding computations in the paper. There is an average of 2,421 burn victims every year in the NCR. This figure decreases to 1,965 after competitor capacities are considered. It is recognized however, the people are becoming more and more conscious about safety, and that the probability of burns occurring may have a decreasing trend in the long term. This fact though, may be offset by the increase in both the population and the number of manufacturing industries in the area. the resulting figures in the market study provide a substantial level of demand that permits the further exploration of the project through a technical study. The details of the venture, such as service schedules, operations, machineries, personnel, facility la-out and location, costs, among others, are established in the technical phase. A very important result in this phase is the determination of the total project cost which amounted to P 33,597,211.88. The advise and assistance of experts in different fields such as medicine, physical therapy, engineering and architecture were availed by the group to make sure that no technicalities are missed-out, and that everything is laid down in as much detail as possible. The systems and procedures of Center operation are specified, this includes the flow of patients, personnel and equipment. The forms to be used in the operation were also made. The prices of the required equipment were taken from actual distributors and all other materials were listed at current prices. The construction of the facility lay-out is such that equipment sizes and space requirements for hospitals are taken into consideration. The location of the Center is situated along South Superhighway, beside the Motorola plant. The size of the land is 1200 square meters and is priced at 12,000 per square meter. There were no irresolvable difficulties encountered in this phase, thus feasibility is easily concluded. The financial analysis which is the last phase of the project, utilizes the results of the market and technical studies. Demands from the market study have been converted to capacities in the technical study. these capacities were used to compute for the total project cost. The pricing scheme was formulated to derive an estimate of gross revenue. All these data were used in the financial analysis to establish financial profitability. Several measures were used for this purpose, namely net income projections, computations of the payback period, internal rate of return and net present value of the project. All of which have produced promising results rendering the project financially feasible.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Burn Rehabilitation Center; Rehabilitation centers; Burns and scalds--Patients--Rehabilitation.; Participatory monitoring and evaluation (Project management)